ANALISIS KEBIJAKAN PARIWISATA PADA PERUSAHAAN PT. HIMALAYA TOURS & TRAVEL DI DAERAH SULAWESI SELATAN - Arsyad Tajuddin (AkMen JURNAL ILMIAH, 2012)
The development of the tourism potential of today have a very good prospect, where the tourism industry became one of the priorities that will be developed and as a revenue contributor south Sulawesi province. However this can not be separated from how the campaign was conducted to provide information to the public, with good information so people will be easier to determine the potential of tourism in south Sulawesi.